The Mediating Effect of Coping Strategies on Religious/Spiritual Struggles and Life Satisfaction - Małgorzata Szcześniak; Zdzisław Kroplewski; Roman Szałachowski (Religions, 2020)
A growing number of researchers are testing potential problematic forms of religiousness that denote anxieties regarding sacred matters. However, only a few studies have assessed how religious/spiritual struggle is associated with positive outcomes. Because people’s coping responses to stressors are key determinants of their well-being, we expected that different coping strategies could be potential mediators between religious problems/tensions and life satisfaction. The research was conducted on a group of 744 Roman Catholics. We used the Religious Comfort and Strain Scale, Satisfaction with Life Scale, and Brief Coping Orientation to Problems Experienced (COPE) questionnaire. The outcomes show that religious comfort correlated positively with life satisfaction, while fear/guilt, negative emotions toward God, and negative social interactions surrounding religion correlated negatively with life satisfaction. Our research amplifies the understanding of the religious/spiritual struggles and life satisfaction relationship, mediated by “secular” coping strategies. It confirms that both religious and secular methods of experiencing different strains seem to coexist with multiple other strategies in the context of broadly understood life satisfaction.